A Study to Evaluate the Impact of Internet Exposure on Academic Performance and Social Behavior of Adolescents: A Narrative Review (International Journal of Nursing Education, 2019)
Introduction: The internet today is a worldwide entity whose nature cannot be easily or simply defined. To many, the internet is a large computer network linking together millions of smaller computers at numerous sites in various countries belonging to thousands of business, government, research, educational and other organizations. To the internet users, the internet is a global community-one with a very active life. In today world, the Internet plays a vital role in the teaching, research and learning process in academic institutions. Thus, the advent of the Internet has heralded the emergence of a new form of knowledge production and distribution – the soft form. Aim: The aim of the study is to assess the impact of internet exposure on academic performance and social behavior of adolescents. Methodology: Intervention: Structured questionnaires and attitude scales. Types of studies: Cross-sectional descriptive research design. Types of participants: Adolescent students. Setting: Selected inter-colleges of Greater Noida. Outcome: This narrative review result has appeared that Internet exposure have adverse impact of academic performance and social behavior of adolescent students.
Keywords: Internet Exposure, Academic Performance, Social Behavior, Adolescent Students.